ANALYSIS OF FACTORS INFLUENCING DEMAND OF SIMPLE HOUSES AT ACEH BESAR REGENCY - Fahmi Fahmi; Abubakar Hamzah; Mohd. Nur Syechalad (Syiah Kuala University, 2018)
AbstractThe objective of this research is to find out the influence of individual income, interest, house price and location regarding on the demand of simple house at Aceh Besar Regency. Analysis method employed in this research was Quantitative Method. Data collecting in this research was Primary Data. The analysis result indicates that the demand of simple houses at Aceh Besar Regency is remarkably high. Individual income and interest give significant influence toward the demanding of the simple houses at Aceh Besar Regency, meanwhile house price and location had less impact regarding the demand of simple houses at Aceh Besar Regency. The government is highly expected to maintain and preserve the subsidy of the interest for the people. Therefore it makes easier for them to get simple houses especially at Aceh Besar Regency, because houses are also basic needs in addition to food and clothing.